2008
DOI: 10.1002/car.1052
|View full text |Cite
|
Sign up to set email alerts
|

Child protection training in sport‐related degrees and initial teacher training for physical education: an audit

Abstract: This article reports on an online survey of child protection training for students on sport-related and Initial Teacher Training Physical Education degrees, and on the views of recently graduated teachers of the usefulness of such training in their everyday work. The results indicate that child protection training is provided in most courses but in varying amounts. Respondents to the survey reported positively, in the main, about the effects of new requirements for teacher training (Every Child Matters: Change… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
38
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(38 citation statements)
references
References 13 publications
0
38
0
Order By: Relevance
“…After applying the inclusion criteria described in the previous section to the 31 pre-service publications, 20 studies reported in a total of 21 publications 25,26,44,61,63,70,81,83,92,94,117,142,148,156,174,189,191,195,200,201,213 were included in the synthesis (one study was reported in two separate publications, 26,156 and data from both of these were extracted for this report), with 10 references 57,67,85,88,116,179,192,199,202,206 being excluded. Table 45 provides an overview of the key characteristics of the included studies.…”
Section: Results Of the Synthesismentioning
confidence: 99%
See 4 more Smart Citations
“…After applying the inclusion criteria described in the previous section to the 31 pre-service publications, 20 studies reported in a total of 21 publications 25,26,44,61,63,70,81,83,92,94,117,142,148,156,174,189,191,195,200,201,213 were included in the synthesis (one study was reported in two separate publications, 26,156 and data from both of these were extracted for this report), with 10 references 57,67,85,88,116,179,192,199,202,206 being excluded. Table 45 provides an overview of the key characteristics of the included studies.…”
Section: Results Of the Synthesismentioning
confidence: 99%
“…In terms of country, the highest percentage of studies were conducted in the UK (n = 9, 25,63,70,83,92,117,142,174,191 45%), followed by Australia (n = 7, 44,94,189,195,200,201,213 35%). There was one study each from Finland, 26,156 Zimbabwe 81 and the USA, 61 with one study not explicit about the country but it most likely being the USA.…”
Section: Characteristics Of the Included Studiesmentioning
confidence: 99%
See 3 more Smart Citations